Effects of particle breakage on the compression behaviour of gap-graded carbonate sand–silt mixtures. Issue 1 (8th March 2021) - Ma, L.; Chiu, C.F.; Cheng, Y.P.; Ren, Y.Z.
Abstract : Isotropic compression tests were conducted on a series of gap-graded mixtures of a carbonate sand (CS) from the South China Sea and a fine crushed quartz silt. The purpose of these tests is to explore breakage mechanism of CS particles under varying fines content (FC). The weaker CS originally exhibited a unique compression line, whereas the stronger quartz silt originally had a stable soil fabric leading to non-convergent compression lines. It was found that the threshold FC indicating a change from CS to silt-dominated soil matrix, together with the suppression of particle breakage, have governed the change from converging to non-converging compression behaviour and from non-stable to stable soil fabric for these gap-graded soil mixtures. For FC ≤ 30%, the soil mixtures exhibited a unique compression line due to the substantial breakage of the weaker CS particles in the CS-dominated soil matrix. However, non-convergent compression lines were observed for the soil mixtures with FC ≥ 40% (threshold FC). It can be explained due to inability of weaker CS particles to participate in load bearing of the silt-dominated soil matrix. There was insignificant particle breakage of the CS with the initial soil fabric remaining stable at high stress.